THE INFLUENCE OF LEADERSHIP AND JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT AT PT MERAPI UTAMA PHARMA MEDAN - Intan Royana Silalahi; Emi Wakhyuni; Livia Fransiska; Maya Sari; Muhammad Baihaqki (Universitas Efarina, 2022)
The research objective was to determine more clearly and analyze the influence of leadership and job satisfaction on organizational commitment at PT Merapi Utama Pharma Medan. The method used is descriptive analysis method and multiple linear regression analysis method, using simultaneous test, test parsiaI and determination analysis. The data used are primary and secondary data. Researchers used 36 respondents in the sample. The results showed 1) Variable influential leadership on organizational commitment at PT. Merapi Utama Pharma Medan. 2) The variables affect job satisfaction to organizational commitment at PT. Merapi Utama Pharma Medan. 3) Variable leadership and job satisfaction simultaneously influence on organizational commitment at PT Merapi Utama Pharma Medan. The test results determinant coefficient (R2) shows that the value of R Square = 0.907 90.7% means the factors affecting organizational commitment at PT Merapi Utama Pharma Terrain can be explained by the leadership and job satisfaction. While the remaining 0.093% can be explained by other factors not examined by this study..